Problems of conceptualization and operationalization of professional success - Pilch, Piotr (Metody i techniki zarządzania. Inspiracje dla teorii i praktyki, 2020)
The aim of the chapter is to present the methodological complexity of the study of the career success concept in the Polish cultural context. This complexity is manifested both in the process of conceptualization of the examined concept and its operationalization. The reasons for this complexity are manifold and will be presented in chronological, socio-cultural and methodological order. The dualism of career success expressed in opposition between the process of its achievement and the result of this process and its objective-subjective nature results in the necessity to construct such methods of measurement that take into account its specific and multidimensional character. The aim of the analyses will be to prove the change of social criteria of career success from those constructed and confirmed socially in favor of individualized assessment dimensions. The existing relatively simple measures of objective professional success are complemented by measures taking into account the perspective of the individual (its system of values, goals, needs) or adopted reference points (significant others) from a comparative perspective.